2019
DOI: 10.1016/j.jid.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 Is a Major Activator of TGF-β Signaling in Recessive Dystrophic Epidermolysis Bullosa Fibroblasts

Abstract: Mutations in the gene encoding collagen VII cause the devastating blistering disease recessive dystrophic epidermolysis bullosa (RDEB). RDEB is characterized by severe skin fragility and nonhealing wounds aggravated by scarring and fibrosis. We previously showed that TSP1 is increased in RDEB fibroblasts. Because transforming growth factor-b (TGF-b) signaling is also increased in RDEB, and TSP1 is known to activate TGF-b, we investigated the role of TSP1 in TGF-b signaling in RDEB patient cells. Knockdown of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…Many of the aggressive SCC of the skin develops in areas with chronic ulcers as in hereditary conditions like epidermolysis bullosa [13,14,26]. The reason for this different behavior is still a subject of controversy and collaborative studies have recently shed light onto the matter [9,17,[27][28][29]. Recently, attention has been focused on a possible role of the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the aggressive SCC of the skin develops in areas with chronic ulcers as in hereditary conditions like epidermolysis bullosa [13,14,26]. The reason for this different behavior is still a subject of controversy and collaborative studies have recently shed light onto the matter [9,17,[27][28][29]. Recently, attention has been focused on a possible role of the stroma.…”
Section: Discussionmentioning
confidence: 99%
“…173 Activated TGF-β can bind to a subset of integrins (including αvβ6, 174,175 αvβ8, 173,176 and αvβ1, 177 ) or bind to the secreted and matricellular protein thrombospondin-1 (TSP-1, which is regarded as the first discovered activator of TGF-β1) under both physiological and pathological conditions in vivo. [178][179][180][181][182] An increased level of TSP-1 secreted by mesenchymal cells, especially Snail-overexpressing cells, on the one hand facilitates the further activation of the TGF-β signaling pathway, thus contributing to a positive feedback effect on EMT. On the other hand, it promotes the continual generation of Foxp3 + Tregs from naive T cells, which antagonize the effects of cytotoxic T lymphocytes (CTLs), together with the induction of impaired dendritic cells (DCs) and inhibition of NK cells within the TME, thus ultimately resulting in resistance to immunotherapy, and even chemotherapy [183][184][185][186] (Fig.…”
Section: Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…Fibrosis is a major pathological complication of RDEB, and work with patient cells in culture, animal models and patients have all identified TGFβ signaling as a major driver of fibrosis and disease severity [9,[72][73][74][75]. TGFβ is a primary mediator of fibrosis driving extracellular matrix (ECM) deposition in numerous pathological situations, and considerable effort has focused on understanding and inhibiting TGFβ in a number of contexts [76].…”
Section: Small Molecules Repurposed To Relieve Symptomsmentioning
confidence: 99%
“…The mechanism here is thought to be a reduction in blood pressure, which reduces the bioavailability or release of TGFβ ligand from the fibrotic ECM. Other preclinical efforts have used viral delivery of decorin, an inhibitor of TGFβ, to show reduced paw fibrosis in mouse models [79], whereas in vitro work with patient cells has suggested that inhibition of thrombospondin-1, a potent activator of TGFβ, may have clinical efficacy [72]. In addition to these academic-led initiatives, a number of anti-TGFβ antibodies are in development in the commercial space that have potential to reach clinical trial in the coming years.…”
Section: Small Molecules Repurposed To Relieve Symptomsmentioning
confidence: 99%